A EFICÁCIA DAS DECISÕES JUDICIAIS NO MARANHÃO: Judicialização da saúde e o acesso às unidades de tratamento intensivo neonatal - Sousa, Lidia Cunha Schramm de (2015)
Widely debated in the Judiciary theme is the Right to Health. The legalization of public health policies is a growing phenomenon throughout the country, and several branches of the judiciary received demands related to health. This discussion is reflected in the three Powers. This dissertation studies the effectiveness of Court decisions in Maranhão, in relation to access at neonatal intensive care units in Maranhão focused on the magistrates' decisions 1 the Childhood and Youth and the consequences of those decisions. The universality and equality in access to neonatal intensive care units are analyzed based on John Rawls literature.